(untitled) (International Journal of Engineering and Computer Science, 2017)
Many cryptographic algorithms (e.g., AES, HMAC) require the establishment of shared keying material in advance. The Federal key agreement schemes document is based on ANSI X9.42 agreement of symmetric keys using discrete logarithm cryptography, ANSI X9.44 key agreement and key transport using factoringbased cryptography and ANSI X9.63 key agreement and key transport using elliptic curve cryptography. It is necessary for the keying material to establish and maintain cryptographic keying relationships. Shared secret is a value computed using a prescribed algorithm and combination of keys belonging to the participants in the key establishment scheme. The public key algorithms like RSA are becoming the standards for the encryption. But the major threat of using RSA is, it is multiplicative and hence does not guarantees the uniqueness of the key and further it does not stand true to the dynamic demands of the system. Practically it is proved that such public key algorithms are slow as compared to the symmetric key algorithms. The PKI has provided a strong platform for the RSA algorithm. In view to overcome above limitations in this article a cryptographic method of key management has been proposed that uses the symmetric key algorithm (Blow fish) over the asymmetric key algorithm (RSA algorithms). The symmetric key algorithms do not have any key management scheme. Further, the proposed work uses ant colony based evolutionary computing algorithm to meet the requirement in which the shared secret value changes dynamically with time and matures with the time as numbers of communications amongst the legitimate users increases. The method proposed has been found have system of key management, which apart from being faster has all the security features. The efficiency in time management in all the aspects namely Key Generation, key Transmission, Key Revocation, Encryption and decryption is found to be much better than the widely used PKI. This speed do not compromise the security aspects of the system, in fact this efficient time management has helped to build up the secured transmission. Practically to avoid the time of encryption and decryption using the public key infrastructure certifying authorities use the session keys that use symmetric key algorithm. This method is not providing any authentication mechanism. The proposed system stands balanced and solves all the problems mentioned above. Overall it is a key management scheme for the symmetric key algorithms.